Letter - Birmingham Trade Union Emergency Committee, 12 May 1926 (page 3)
1926-05-12 "Letter - Birmingham Trade Union Emergency Committee, 12 May 1926 (page 3)" [g0371003.jpg], 12 May 1926, Birmingham Trade Union Emergency Committee